IMPLEMENTASI PEMBELAJARAN SAINS BERBASIS INKUIRI DAN PENGARUHNYA TERHADAP LIFE SKILLS (KECAKAPAN HIDUP) DITINJAU DARI PENGETAHUAN KEISLAMAN MAHASISWA - Ramdhani Sucilestari (Jurnal Tatsqif, 2018)
This study aims to determine the effect of the inquiry learning model which is integrated through Islamic knowledge on student life skills. The research method used was a quasi-experimental method with a 2x2 factorial research design through a posttest-only control group design procedure. The population in this study were all Semester V students of the PGMI Department of UIN Mataram Academic Year 2017/2018 with 224 students divided into seven different classes. In this study, the samples were students of class V C as the experimental class and students of class V E as the control class. Each class contains 32 students for class VI C and 32 students in class VIE so that the total number of students sampled is 64 students. The research instruments in the form of Islamic knowledge tests, academic skills, personal skills, and vocational skills observation sheets were given at the end of the study. Data from the research results were analyzed by Manava in two ways. The results showed that: 1) the implementation of inquiry-based Science learning models had an effect on student life skills, 2) Islamic knowledge had no effect on student life skills, and 3) There was no interaction effect on the implementation of inquiry-based Science learning models and Islamic knowledge on student life skills. The inquiry-based learning model is an alternative learning model that can be implemented to foster student life skills in college or students in school especially in learning related to science.